Novelist Poets in Palestine 1948 - 2013 - Omar Said Abdul Jabbar Al-Quzoq (My University, 2014)
This Study traces a modern literary phenomenon, and focuses on poets shifting interest from poems to novels, backing the idea that says: the novel has become the collection of modern Arab writers. The study allocated in its shifting from general to special, and from theory to practice in occupied Palestine as a place, and the "Nakba" as period of time. Therefor the study included fifteen poets whom general conditions applied to them with regard to this phenomenon. Then among them I limited objective and technical analysis to eight novels which the phenomenon and its conditions is manifested to them. Therefor the study was divided in dealing with this phenomenon to; introduction, preface, four chapters and conclusion. The introduction intended to formulate a series of questions that constitute the study columns. Emanating from those dim voices that believe in this phenomenon, then exposed the parts of the chapters and the study method, and related comparative studies. In preface I addressed the beginnings of shifting in literary sequence between poetry and novel, with consideration that poetry is the Arab collection, and the novel was introduced to compete this feature. I highlighted opinions of critics addresse this issue either old or modern; also the disregarders and inferiority look to novel compared to poetry. And later the Superiority of novel on poetry. So that the preface formed an iterance depending on the research proposal by presenting the following question:- If literature, both poetry and narrative expresses a tale, this means literature itself is a tale that has its events, time, place, characters and heroes, plot and siftings. If the sentence (qifa nabki)" stop to cry" is a hero of the first part of literature story, would Najeeb Mahfouz's opinion (novel is the modern world poetry) a hero of the second part of this tale? In the first chapter I addressed the shifting of many well-known poets from poetry to novel or adopting both. I also dealt with the interference between both poetry and novel in old and recent times. I exposed spreading this phenomenon not only in Palestinian poets but also in Arab poets, even the whole world poets through indicators of international awards such as Nobel award for literature which favors poetry rather than novel, or by focusing on important poets who introduced novel in their poems. I listed this in the research index. Finally I presented the important reasons that brought about less interest in poetry comparing this with reasons that causes increase in novel emergence and acceptance. The second chapter was more specific I dealt with effects of shifting phenomenon and pairing between poetry and novel in Palestine practically and theoretically in the two centuries past and present, trying to prove its depth and reflection on Palestinian poets, also exposing Palestinian critics' opinions on this shifting. Also opinions of poets themselves in feeling this phenomenon, through their answers to a series of questions listed in the index for which I conducted analytical and statistical study to find evidences. In the third chapter, I focused on the most important issues in novels, then analyzed and criticized them, also added related critics opinions. I also dealt with novels of those who were well known for their poetry among the fifteen poets listed in the research index. I allocated the last forth chapter for architecture of novels, starting with literary naturalization of novelists poets novels and their relationship telling Biography and Novella through the techniques of novel narration and how achieved in these novels ending with the poetry language issue in it. Finally I ended the research with a conclusion summarized the most important results the study reached.

تقوم الدراسة على تتبع ظاهرة أدبية حديثة، تُعنى بانتقال الشعراء من الشعر إلى الرواية، وذلك استنادا إلى مقولة: أن الرواية أمست ديوان العرب المحدثين. وقد خصصت الدراسة، في انتقالها من العام إلى الخاص، ومن النظرية إلى التطبيق، فلسطين المحتلة مكانا، وما بعد النكبة زمانا لها. لذا فقد اشتملت الدراسة على خمسة عشر شاعرا، ممن تنطبق عليهم الشروط العامة لهذه الظاهرة، ثم قصرت تحليلها الموضوعي والفني على روايات ثمانية من بينهم، ممن تجلت فيهم الظاهرة وشروطها أكثر من غيرهم. وعليه، فقد قُسمت الدراسة، في تناولها لتلك الظاهرة، إلى: مقدمة وتمهيد وأربعة فصول وخاتمة: حيث عمدت المقدمة إلى صياغة مجموعة من الأسئلة، تشكل أعمدة الدراسة، وتنطلق من تلك الأصوات الخافتة المنادية بالظاهرة، ثم أفصحت عن تقسيمات الفصول، ومنهج الدراسة، وما قاربها بصلة من دراسات سابقة. أما التمهيد فقد تناولت فيه بواكير التحول في التراتب الأدبي بين الشعر والرواية، على اعتبار أن الشعر هو ديوان العرب، وأن الرواية قدمت لتزاحمه هذه الميزة. وأبرزت الآراء النقدية التي تناولت هذه المسألة، قديمها وحديثها، والنظرة الدونية التي كان ينظر فيها للرواية إزاء الشعر، ثم رجحان كفة الرواية على الشعر. ليشكل التمهيد مدخلا تقوم عليه فرضية البحث، بطرحه للسؤال التالي: إذا كان الأدب، بشقيه الشعري والسردي، يعبر عن حكاية، فإنه بحد ذاته حكاية لها أحداثها وزمانها ومكانها وشخوصها وأبطالها وحبكتها وتحولاتها. فإذا كانت عبارة " قفا نبك " بطلا للجزء الأول من حكاية الأدب، فهل سيكون رأي نجيب محفوظ " الرواية شعر الدنيا الحديثة " بطلا للجزء الثاني لهذه الحكاية؟ وأما الفصل الأول فقد وقفت فيه على مسألة تحول كثير من الشعراء، المعروفين بأصلهم الشعري، من الشعر إلى الرواية، أو المزاوجة بينهما، وذلك من خلال الوقوف على مسألة التقاطع بين الشعر والرواية، قديما وحديثا، وتناول مسألة امتدادها، ليس فقط على مستوى شعراء فلسطين، وإنما لتطال شعراء الوطن العربي، والعالم أجمع. وذلك من خلال مؤشرات الجوائز العالمية، كجائزة نوبل للآداب، التي أمست الحظوة فيها للشعر على الرواية، أو من خلال إبراز أهم الشعراء الذين داخلت الرواية نتاجهم الشعري، أو طغت عليه، وأدرجت ذلك في ملاحق البحث، ثم وقفت على أهم الأسباب التي أدت إلى أفول الشعر، وخفوت تلقيه، ومقارنتها بالأسباب التي عملت على سطوع الرواية، وتصاعد الإقبال عليها. وأما الفصل الثاني فقد جاء أكثر تخصيصا، حيث تناولت فيه صدى ظاهرة التحول أو المزاوجة بين الشعر والرواية في فلسطين ممارسة وتنظيرا، وذلك من خلال الامتداد الزمني لها في القرنين؛ المنصرم والحالي، في محاولة لإثبات تجذرها، وانعكاسها على شعراء فلسطين، وبيان آراء النقاد الفلسطينيين في هذا التحول، وآراء الشعراء أنفسهم في ملامسة الظاهرة لهم، وذلك من خلال إجاباتهم عن مجموعة من الأسئلة، تم إدراجها في قائمة الملاحق، وأجريت لها دراسة تحليلية وإحصائية، للوقوف على دلالاتها، بين صفحات الفصل. وأما الفصل الثالث فقد عرجت فيه على أهم الموضوعات التي تناولتها الروايات، وتناولتها بالتحليل والنقد، وأبرزت آراء النقاد فيها، وقد وقفت على روايات أكثر من تجذّر فيهم شعرا، من بين الشعراء الروائيين الخمسة عشر المدرجين ورواياتهم في ملاحق البحث. وأما الفصل الرابع فقد خصصته للمعمار الفني للروايات، ابتداء بالتجنيس الأدبي لروايات الشعراء الروائيين، وعلاقتها برواية السيرة الذاتية، وبالنوفيلا. ومرورا بتقنيات السرد الروائي، ومدى تحققها في تلك الروايات، وانتهاء بمسألة اللغة، ومدى تحقق الشعرية فيها. ثم أنهيت البحث بخاتمة لخصت فيها أهم النتائج التي توصلت إليها الدراسة.
الشعراء الروائيون في فلسطين(1948 ـ 2013)